Examining the Relationships between Student Engagement, Campus Facilities, and Technology Integration among Elementary Teacher Candidates - Selim Günüç; Emrullah Yiğit; Hüseyin Artun; Murat Okur (Universitas Pendidikan Indonesia, 2022)
This study aims at examining the relationships between technology integration, campus facilities, and student engagement at 26 state universities in Turkey. In the study, the quantitative method was employed, specifically the correlational research method. The research sample involved 5,534 female students (71.21%) and 2237 (28.79%) male students, amounting to 7771 participants in total. The data of this study were collected by means of Student Engagement Scale, Student Perception Scale for Faculty Members’ Technology Integration Efficacy, and Campus Climate Checklist. In addition, Pearson correlation analysis was conducted on the collected data. The results revealed that in every university, there was a positive relationship between student engagement and the students’ scores in regards to benefits from the campus facilities. Another important result was that the positive relationship between student engagement and the students’ perceptions regarding technology integration efficacies of the faculty members was proven for all universities involved in the study.